Significant Improvement of Passivation Performance by Two-Step Preparation of Amorphous Silicon Passivation Layers in Silicon Heterojunction Solar Cells - 张悦 郁操 杨苗 张林睿 何永才 张津燕 徐希翔 张永哲 宋雪梅 严辉 (Chinese physics letters, 2017)
The key feature of amorphous/crystalline silicon heterojunction solar cells is extremely low surface recombination, which is related to superior passivation on the crystalline silicon wafer surface using thin hydrogenated amorphous silicon （a-Si：H） layers, leading to a high open-circuit voltage. In this work, a two-step method of a-Si：H passivation is introduced, showing excellent interface passivation quality, and the highest effective minority carrier lifetime exceeds 4500μs. By applying a buffer layer deposited through pure silane plasma, the risk of film epitaxial growth and plasma damage caused by hydrogen diluted silane plasma is effectively reduced. Based on this, excellent passivation is realized through the following hydrogen diluted silane plasma process with the application of high density hydrogen. In this process, hydrogen diffuses to a-Si/c-Si interface, saturating residual dangling bonds which are not passivated by the buffer layer. Employing this area of 239 cm2 is prepared, yielding to open-circuit voltage two-step method, a heterojunction solar cell with an up to 735mV and total-area efficiency up to 22.4%.